Nerve Repair Using Decellularized Nerve Grafts in Rat Models. A Review of the Literature - Lovati, Arianna B.; D’Arrigo, Daniele; Odella, Simonetta; Tos, Pierluigi; Geuna, Stefano; Raimondo, Stefania (Frontiers in Cellular Neuroscience, 2018)
Peripheral nerve regeneration after severe traumatic nerve injury is a relevant clinical problem. Several different strategies have been investigated to solve the problem of bridging the nerve gap. Among these, the use of decellularized nerve grafts has been proposed as an alternative to auto/isografts, which represent the current gold standard in the treatment of severe nerve injury. This study reports the results of a systematic review of the literature published between January 2007 and October 2017. The aim was to quantitatively analyze the effectiveness of decellularized nerve grafts in rat experimental models. The review included 33 studies in which eight different decellularization protocols were described. The decellularized nerve grafts were reported to be immunologically safe and able to support both functional and morphological regeneration after nerve injury. Chemical protocols were found to be superior to physical protocols. However, further research is needed to optimize preparation protocols, including recellularization, improve their effectiveness, and substitute the current gold standard, especially in the repair of long nerve defects.